A Narrative Review of the Integration of Big Data Analytics and Business Intelligence in Organizational Decision-Making - Noviany , Henny (Data : Journal of Information Systems and Management, 2025)
The integration of Big Data Analytics (BDA) and Business Intelligence (BI) has become increasingly vital for enhancing strategic decision-making within contemporary organizations. This narrative review aims to investigate how the convergence of BDA and BI influences decision-making processes, particularly in sectors such as finance, healthcare, manufacturing, and retail. The review employed comprehensive literature searches across Scopus, Web of Science, and Google Scholar using keyword combinations like “Big Data Analytics”, “Business Intelligence”, and “Decision Making”. Inclusion criteria prioritized peer-reviewed journal articles from the past decade. Findings reveal that BDA enables organizations to analyze large-scale data for hidden insights, while BI transforms these insights into visual and actionable intelligence. Together, they contribute to increased decision accuracy, cost reduction, and enhanced performance. Artificial Intelligence (AI), particularly machine learning and natural language processing, further amplifies these outcomes by enabling rapid and nuanced analysis of structured and unstructured data. However, systemic barriers persist, including fragmented data infrastructure, limited human capital, and concerns over data ethics and compliance. This review highlights the need for organizations to adopt a holistic, cross-functional approach to data integration while investing in digital skills development. It also underscores the importance of regional readiness and industry-specific strategies. The findings inform policymakers, practitioners, and scholars on the strategic imperatives for integrating BDA and BI to sustain innovation, responsiveness, and competitive advantage in the digital age